Functional Polymers and Polymeric Materials From Renewable Alpha-Unsaturated Gamma-Butyrolactones - Kollár, Jozef; Danko, Martin; Pippig, Falko; Mosnáček, Jaroslav (Frontiers in Chemistry, 2019)
Sustainable chemistry requires application of green processes and often starting materials originates from renewable resources. Biomass derived monomers based on five-membered γ-butyrolactone ring represent suitable candidates to replace sources of fossil origin. α-Methylene-γ-butyrolactone, β-hydroxy-α-methylene-γ-butyrolactone, β- and γ-methyl-α-methylene-γ-butyrolactones bearing exocyclic double bond are available directly by isolation from plants or derived from itaconic or levulinic acids available from biomass feedstock. Exocyclic double bond with structural similarity with methacrylates is highly reactive in chain-growth polymerization. Reaction involves the linking of monomer molecules through vinyl double bonds in the presence of initiators typical for radical, anionic, zwitterionic, group-transfer, organocatalytic and coordination polymerizations. The formed polymers containing pendant ring are characterized by high glass transition temperature (Tg > 195 oC) and render decent heat, weathering, scratch and solvent resistance. The monomers can also be hydrolyzed to open the lactone ring and form water-soluble monomers. Subsequent radical copolymerization in the presence of cross-linker can yield to hydrogels with superior degree of swelling and highly tunable characteristics, depending on the external stimuli. The five-membered lactone ring allows copolymerization of these compounds by ring opening polymerization to provide polyesters with preserved methylene functionality. In addition both the lactone ring and the methylene double bond can be attacked by amines. Polyaddition with di- or multi-amines leads to functional poly(amidoamines) with properties tunable by structure of the amines. In this mini-review we summarize the synthetic procedures for preparation of polymeric materials with interesting properties, including thermoplastic elastomers, acrylic latexes, stimuli sensitive superabsorbent hydrogels, functional biocompatible polyesters and poly(amidoamines).